Socioeconomic Status and Child Maltreatment: A Critical Literature Review - Hamed Nazari; James C. Oleson; Irene De Haan (Social Sciences, 2025)
A robust body of research examines the association between socioeconomic status (SES), particularly its economic dimension, income poverty, and child maltreatment rates. However, several key questions regarding this relationship remain underexplored. Utilizing a critical literature review, this article finds that some forms of child maltreatment (i.e., sexual abuse) do not correlate with income poverty. Moreover, evidence about the effects of other dimensions of SES, including employment and education is not monolithic. The complexity of this relationship is further influenced by the data source and unit of analysis. Studies using administrative data and analyzing SES at the family or household level frequently report a strong correlation between SES and child maltreatment. However, this relationship weakens (or in some cases disappears) when examined at the neighborhood or regional level using self-report data. Our findings also suggest that the overrepresentation of minority groups in child maltreatment statistics can be, at least in part, attributed to economic disadvantages. Furthermore, social cohesion appears to buffer the effects of income poverty and material hardship, highlighting the role of inequality in weakening social networks and exacerbating socioeconomic stressors. A developing body of literature demonstrates the link between income inequality and child maltreatment rates and indicates that policies aimed at addressing the impact of SES on child maltreatment should not only focus on alleviating poverty-related factors, such as material hardship, unemployment, and housing instability, but also target broader class disparities as the common root of many social problems.